Ultrastructure of the liver microcirculation influences hepatic and systemic insulin activity and provides a mechanism for age‐related insulin resistance. Issue 4 (20th April 2016) - Mohamad, Mashani; Mitchell, Sarah Jayne; Wu, Lindsay Edward; White, Melanie Yvonne; Cordwell, Stuart James; Mach, John; Solon‐Biet, Samantha Marie; Boyer, Dawn; Nines, Dawn; Das, Abhirup; Catherine Li, Shi‐Yun; Warren, Alessandra; et al.
Summary: While age‐related insulin resistance and hyperinsulinemia are usually considered to be secondary to changes in muscle, the liver also plays a key role in whole‐body insulin handling and its role in age‐related changes in insulin homeostasis is largely unknown. Here, we show that patent pores called 'fenestrations' are essential for insulin transfer across the liver sinusoidal endothelium and that age‐related loss of fenestrations causes an impaired insulin clearance and hyperinsulinemia, induces hepatic insulin resistance, impairs hepatic insulin signaling, and deranges glucose homeostasis. To further define the role of fenestrations in hepatic insulin signaling without any of the long‐term adaptive responses that occur with aging, we induced acute defenestration using poloxamer 407 (P407), and this replicated many of the age‐related changes in hepatic glucose and insulin handling. Loss of fenestrations in the liver sinusoidal endothelium is a hallmark of aging that has previously been shown to cause deficits in hepatic drug and lipoprotein metabolism and now insulin. Liver defenestration thus provides a new mechanism that potentially contributes to age‐related insulin resistance.